Assessment of the Readiness of Guidance Counselling Professionals in Adapting to Technology in their Practice in Institutions of Learning in Katsina State, Nigeria - Mohammed, Lawal Ahmed; Usman, Abdu; Mustapha, Ismail (Journal of Innovation in Education and Social Research, 2024)
The research examined the readiness of Guidance Counselling professionals to embrace technology in tertiary educational institutions in Katsina State. Four objectives and four research questions guided the study. The study adopted a survey design for the study. Ten (10) tertiary institutions and six two (62) counselors formed the sample of the study. One validated instrument with a reliability coefficient of 0.78 named Readiness of Counselling Professional to adapt to technology in their Practice guided data collection. Data analysis was conducted by providing answers to the study's research questions, where each statement was rated using a simple majority percentage rule, and statements with higher percentages were accepted. The study reveals that guidance counseling professionals in tertiary institutions in Katsina State possess a high level of technological literacy and hold positive attitudes towards adopting technology in their practices. However, significant barriers hinder the effective adoption of technology. Furthermore, the current state of technology integration is inadequate, the study recommends that educational institutions should invest in technology infrastructure, additional training and support, guidelines, and policies that sustain the effective use of technology in Counselling services.